Defining guidelines for ditch depth in drained Scots pine dominated peatland forests - Hökkä, Hannu; Laurén, Ari; Stenberg, Leena; Launiainen, Samuli; Leppä, Kersti; Nieminen, Mika (Suomen metsätieteellinen seura, 2021)
We used a process-based hydrological model SUSI to improve guidelines for ditch network maintenance (DNM) operations on drained peatland forests. SUSI takes daily weather data, ditch depth, strip width, peat properties, and forest stand characteristics as input and calculates daily water table depth (WTD) at different distances from ditch. The study focuses on Scots pine (Pinus sylvestris L.) dominated stands which are the most common subjects of DNM. Based on a literature survey, and consideration of the tradeoffs between forest growth and detrimental environmental impacts, long term median July–August WTD of 0.35 m was chosen as a target WTD. The results showed that ditch depths required to reach such WTD depends strongly on climatic locations, stand volume, ditch spacing, and peat thickness and type. In typical ditch cleaning areas in Finland with parallel ditches placed about 40 m apart and tree stand volumes exceeding 45 m3 ha–1, 0.3–0.8 m deep ditches were generally sufficient to lower WTD to the targeted depth of 0.35 m. These are significantly shallower ditch depths than generally recommended in operational forestry. The main collector ditch should be naturally somewhat deeper to permit water outflow. Our study brings a firmer basis on environmentally sound forestry on drained peatlands.
Keywords: metsämänty; pohjavesi; turve; kunnostusojitus; ojat; metsänhoito; suot; metsämänty; pohjavesi; turve; kunnostusojitus; ojat; metsänhoito; suot